An Analysis of the Supply Chain Model for Production System Under Selling Price Demand Rate, Controllable Deterioration Rate With Several Market Demand - Singh, Krapal; Sharma, Kailash Chandra; Hariom; Singh, Dharamender (Communications in Mathematics and Applications, 2023)
Stock is one of the significant elements of an e-business enterprise for its successful functioning and profitable execution. This research looks into an inventory model for fading gadgets with an ordinary deterioration rate. This paper develops a deterministic inventory model for spoiling items in which shortages are not allowed for declining things. As in applied eventualities, the demand for an object is related to its selling price. It is assumed to be a price-dependent demand. The uniqueness of this article is that the demand rate is selling price dependent, the preservation technique described here was applied for multiple market demands. The study highlights that the model is explained analytically by minimizing the total inventory cost and maximizing the profits incurred. Sensitivity analysis is implemented to show the effect of deviations in the various parameters for the finest solution. The model’s study indicates that the model’s explanation is relatively stable and can be applied to optimizing the entire inventory cost of deteriorating items. The inventory model discussed in this article has controllable deterioration rates. This model helps business enterprises find the finest replenishment plan for raw things and the production strategy for complete products.